(untitled) (Architecture Image Studies, 2025)
This study examines the role of government intervention in promoting ecotourism and agritourism development across 63 provinces in Vietnam from 2015 to 2023. Despite growing recognition of sustainable tourism’s potential, the specific mechanisms through which government policies influence ecotourism and agritourism outcomes remain underexplored in developing country contexts. Using panel data regression with fixed effects and two-stage least squares (2SLS) instrumental variable estimation to address endogeneity concerns, we analyze how government expenditure, regulatory quality, infrastructure investment, and institutional capacity affect tourism sustainability indicators. Our findings reveal that provincial government spending on environmental protection and rural development has significant positive effects on both ecotourism arrivals (β = 0.284,p < 0.01) and agritourism revenue (β = 0.312,p < 0.01). Regulatory quality and institutional capacity emerge as critical moderating factors, with stronger governance amplifying policy effectiveness. However, we identify an inverted U-shaped relationship between government intervention and tourism sustainability, suggesting optimal intervention thresholds beyond which diminishing returns occur. The study contributes to the literature by providing empirical evidence on government-tourism dynamics in a transitional economy context and offers actionable policy recommendations for balancing state guidance with market mechanisms in sustainable tourism development.